Prevalence of stress and its associated factors among secondary boarding school students in Kelantan - Wahab, Faziana (2019)
Introduction Stress is a common problem in adolescence nowadays and students in boarding schools is said to have more stressors as they lived in academically challenged situation compared to students in normal school. There are several factors that associates or increase the tendency to develop stress among these adolescent. There are many studies conducted among adolescents regarding prevalence of stress, the stressors and coping mechanism of stress. There is paucity of specific study conducted to find out the associated factors of stress among adolescents especially in Malaysia. Thus, this study aimed to determine the prevalence and associated factors for stress among secondary boarding school students in Kelantan. Objectives To determine the prevalence of stress and its associated factors among secondary boarding school students in Kelantan Methodology This is a cross-sectional study involving 519 students from conventional and religious boarding schools in Kelantan. The students were required to answer a set of questionnaire on sociodemographic, General Health Questionnaire to assess the distress level, Brief COPE questionnaire for coping mechanism and Hatta Islamic Religiosity Score 96 (HIRS96) questionnaire for religiosity assessments. Data was analysed using simple and multiple logistic regression. Results The prevalence of stress among secondary boarding school students in Kelantan was 21.8%. Sex [OR (95% CI): 1.76 (1.05, 2.95)], view towards family [OR (95% CI): 1.74 (1.04, 2.90)] and coping mechanism of active coping [OR (95% CI): 0.82 (0.69, 0.98)], behavioural disengagement [OR (95% CI): 1.30 (1.06, 1.58)] and self blame [OR (95% CI): 1.29 (1.11, 1.49)] were found to be significantly associated with stress among the students. Conclusion The prevalence of stress among secondary boarding school students in Kelantan was similar to what predicted by WHO and this mental health issue should be tackled seriously by the health professionals, educational provider and parents aiming to reduce and prevent the occurrence of stress among our adolescents.